Challenges for the adoption of ICT for diabetes self‐management in South Africa. Issue 5 (15th August 2019) - Petersen, Fazlyn; Brown, Afeefa; Pather, Shaun; Tucker, William D.
Abstract: The increasing disease burden in developing countries inhibits the provision of quality care to citizens. However, the increased availability of information communication and technology (ICT) tools makes this a viable option for inclusion in primary health care. Even so, barriers are impeding the successful adoption and usage of ICT tools in health care contexts. This research focuses on one such context to identify the challenges and barriers for the adoption of ICT tools for diabetes self‐management in the Western Cape province of South Africa. The extended technology acceptance model (TAM) and four factors (educational, technological, economic, and sociocultural factors) were identified as a basis for investigation. Evidence was gathered from a sample of 131 diabetic patients using semistructured interviews. These factors, together with TAM constructs, explore how patients interact with ICT and their attitudes towards the use of ICT for diabetes self‐management. The results indicate that all four factors form barriers to ICT adoption for diabetes self‐management. These findings provide a basis to inform how future interventions at the primary health care level may be developed to overcome the identified barriers in efforts to integrate ICT tools into diabetic patients' daily self‐management routines.